2018
DOI: 10.1139/as-2017-0053
|View full text |Cite
|
Sign up to set email alerts
|

Multiyear variations in High Arctic river temperatures in response to climate variability

Abstract: Water temperature measurements (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016) from two small rivers in the High Arctic were analyzed to determine the effects of climate variability on thermal regime and the sensitivity to climate change. The East and West rivers (unofficial names) drain similar watersheds (11.6 and 8.0 km 2 , respectively) and are located at the Cape Bounty Arctic Watershed Observatory (CBAWO), Melville Island, Canada (74°55′N, 109°35′W). Differences in seasonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…In this regard, we want to highlight the importance that ongoing collection of field data has on supporting both empirical and model-based studies. In addition, in headwater catchments at high latitudes or elevations, long-term and spatially distributed studies are extremely rare (e.g., Bolduc & Lamoureux, 2018). Therefore, we believe that in future studies, long-term data sets (in alpine headwater catchments) in combination with models should be used to: (c) provide specific tools to assist catchment managers to evaluate and apply suitable management strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, we want to highlight the importance that ongoing collection of field data has on supporting both empirical and model-based studies. In addition, in headwater catchments at high latitudes or elevations, long-term and spatially distributed studies are extremely rare (e.g., Bolduc & Lamoureux, 2018). Therefore, we believe that in future studies, long-term data sets (in alpine headwater catchments) in combination with models should be used to: (c) provide specific tools to assist catchment managers to evaluate and apply suitable management strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Another important limitation that future studies should try to overcome is related to the timespan considered. The study provided useful insights on the thermal response of streams to hydrologic and atmospheric processes; however a short-term study such as ours cannot be confidently employed to identify any long-term trend or assess climate change impacts (Bolduc & Lamoureux, 2018), revealing the importance of long-term hydrologic and thermal monitoring (e.g., Rasouli et al, 2019).…”
Section: Study Limitationsmentioning
confidence: 99%
“…Finally, we calculated thermal sensitivity, which is a measure quantifying how streams respond to air temperature variation and an important metric for understanding the thermal stability of streams (Snyder et al 2015;Bolduc and Lamoureux 2018). Streams with low to moderate thermal sensitivity (0.10-0.45) are defined as thermally resilient because they have more stable stream temperatures throughout the year due to minimal effects imposed by changes in air temperature.…”
Section: Bull Trout Thermal Metricsmentioning
confidence: 99%
“…However, at higher latitudes, perennial groundwater discharge in some streams attenuates the magnitude of freezing, creating areas that are ice free or do not completely freeze to the bottom (Utting et al 2013;Crites et al 2020). This phenomenon is reflected in the thermal sensitivity of streams, whereby as perennial groundwater contributions increase, thermal sensitivity declines (Kelleher et al 2012;Bolduc and Lamoureux 2018;Hare et al 2021). Given that perennial groundwater is the primary mechanism preventing shallow (< 1.5 m) streams from freezing at higher latitudes (Utting et al 2013), it follows that streams which remain unfrozen in the winter should have lower thermal sensitivity.…”
Section: Data Analysesmentioning
confidence: 99%
“…Specifically, the current observed warming in the northeastern region of Canada (and more broadly, the entire Arctic) is directly attributable to anthropogenic forcing (Ding et al, 2014). Changes in the snowmelt onset (Foster et al, 2008), spatial precipitation patterns (Vaughan et al, 2013) and permafrost thaw (Hinzman et al, 2005) related to this warming will inevitably impact freshwater systems with substantial socio‐ecological implications (Bolduc & Lamoureux, 2018; Dugdale et al, 2018; Hill et al, 2014; van Vliet et al, 2013). Global hydrological model simulations have shown that Arctic basins will experience notably higher flows due to significant increases in precipitation and snowmelt (van Vliet et al, 2013).…”
Section: Introductionmentioning
confidence: 99%